What are Ranch Rodeos? - Randy Peterson (Symphony in the Flint Hills, 2010)
Cowboys have always had a sense of competitiveness with one another. They seem to watch what others accomplish and say, “Well, that was pretty good but I think I could have done it better.” Hence, the sport of Ranch Rodeo evolved.
Keywords: Cowboys; ranches; rodeos; horses; cattle; travel; events; jobs; branding; cow; milking; everyday life; competition; talent